Brugada syndrome clinical update. Issue 4 (8th August 2021) - Rojas, Rhadames; Kaul, Risheek; Frenkel, Daniel; Hoch, Ethan G; Iwai, Sei; Jacobson, Jason T; Aronow, Wilbert S.
ABSTRACT: Brugada syndrome (BrS) was initially described in southeast Asians with a structurally normal heart presenting with polymorphic ventricular tachycardia and fibrillation. This condition is marked by J-point elevation ≥ 2 mm with coved-type ST segment elevation followed by negative T wave inversions in at least one precordial lead (V1 or V2) when other etiologies have been excluded. These changes on electrocardiogram (EKG) can either be spontaneous or manifest after sodium channel blockade. The worldwide prevalence of BrS is about 0.4%; however, it is higher in the Asian population at 0.9%. This article will review the current hypotheses regarding the pathophysiology, spectrum of clinical presentation, strategies for prevention of sudden cardiac death and the treatment for recurrent arrhythmias in BrS.